The Future of Evaluation
XVIII, 393 p.
Keywords: Evaluation has become an important instrument for rational governance and is used in an increasing number of countries and policy fields. Recent developments at the global, national and local level are changing the conditions and functions of evaluation worldwide. This book examines current global development trends and changing demands for evaluation. It addresses issues surrounding professionalisation and globalisation, examining the need to strengthen accountability for social development in various different policy fields, regions and countries to improve governance and its impacts on social betterment. It also considers issues of quality, utility and further education and the upgrading of evaluation in a broad variety of different organisations, such as multilateral donor organisations, national public administrations, private consultancies, civil-society organisations, universities, and research institutes. With contributions from 30 different countries, this book combines a broad variety of viewpoints to examine the global future of evaluation.